2020
DOI: 10.1136/bmjsrh-2019-200460
|View full text |Cite
|
Sign up to set email alerts
|

Surgical or medical abortion of pregnancies between 13+0and 23+6weeks’ gestation? A systematic review and new NICE national guidelines

Abstract: BackgroundAbortion in the second trimester may be performed surgically or medically. The objective of this systematic review was to examine the effectiveness, safety and acceptability/satisfaction of surgical compared with medical abortion of pregnancy between 13+0 and 23+6 weeks’ gestation for a new national guideline.MethodsWe searched Embase, Medline and the Cochrane Library on 4 March 2019. We included randomised controlled trials (RCTs; any size) and non-randomised comparative studies with n≥100 in each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…When local legal and practice regulations evolve to allow medication abortion provision outside hospital settings, selection or continuation of hospital-based surveillance will underestimate the number of abortions, overestimate the proportion of surgical abortions, and will systematically capture more complex abortion cases occurring at later gestational ages. This type of selection process has previously been demonstrated to induce selection bias [27,28]; hospitalonly abortion surveillance will overestimate the frequency of second trimester and surgical abortion (relative to first trimester medication abortion) and will overestimate the risk of abortion complications [29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…When local legal and practice regulations evolve to allow medication abortion provision outside hospital settings, selection or continuation of hospital-based surveillance will underestimate the number of abortions, overestimate the proportion of surgical abortions, and will systematically capture more complex abortion cases occurring at later gestational ages. This type of selection process has previously been demonstrated to induce selection bias [27,28]; hospitalonly abortion surveillance will overestimate the frequency of second trimester and surgical abortion (relative to first trimester medication abortion) and will overestimate the risk of abortion complications [29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with D&E, medical abortion has higher risk of retained products requiring surgical intervention [relative risk (RR): 4.58, 95% confidence interval (CI): 1.07-19.64], but not an increased risk of hemorrhage or transfusion. 35 In evaluating the evidence to generate new National Institute for Health and Care Excellence (NICE) guidelines for the United Kingdom, Schmidt-Hansen et al 35 found rates of hemorrhage requiring transfusion, uterine injury, cervical laceration requiring repair, and infection within 1 month 24 1.7% serious adverse events* 25 0.04%-0.28% uterine rupture 21 0.2% requiring major surgery 26 0.1%-0.6% hemorrhage requiring blood transfusion 21 0.2%-0.7% reaspiration 23,27 1% cervical laceration 27 0.8% signs of infection 27 0.2%-0.5% confirmed or suspected uterine perforation 21,27 0.002% adverse reaction to paracervical anesthesia 27 Hospital resources Almost always inpatient 24-48 h stay †…”
Section: Recommended Methods Of Abortionmentioning
confidence: 99%
“…Where both abortion techniques are available, women should receive their preferred method 34,35. Data from randomized controlled trials comparing D&E and medical abortion (MA) are sparse, as individuals often have strong preferences regarding mode of abortion which makes study recruitment almost impossible 36,37.…”
Section: Recommended Methods Of Abortionmentioning
confidence: 99%
See 2 more Smart Citations